Effect of Process Parameters on Tribological Properties of Ti6Al4V Surfaces Manufactured by Selective Laser Melting - Sagbas, Binnur; Gencelli, Goktug; Sever, Ahmet (SPRINGER, 2021)
Selective laser melting (SLM) is one of the most widely used metal additive manufacturing method which is based on powder bed fusion technology and provides opportunity to generate near net shape complex geometries from their CAD data. Surface quality of the SLM manufactured parts is highly affected by process parameters; however, effect of these parameters on the tribological properties has not been fully understood, and optimal process parameters have not been defined yet. In this study, four different SLM parameters; scanning angle, laser power, scanning speed and hatch distance were applied at three different levels for manufacturing Ti6Al4V disk samples as ball-on-disk test coupon. Dry sliding wear behavior of the samples against alumina counter balls were defined under 10 N loading. For determining optimal parameter set and defining the effect of each parameter on the tribological properties, Taguchi's L9 orthogonal array and analysis of variance were used. The results were revealed that scanning angle was the most effective parameter on the tribological behavior of the SLM manufactured Ti6Al4V surfaces. Then scanning speed, laser power and hatch distance came, respectively.
Keywords: additive manufacturing (AM); selective laser melting (SLM); surface integrity; tribology; Ti6Al4V; Materials Science